Uji Kualitas Yoghurt Dengan Penambahan Bahan Lokal Pati Umbi Garut (Maranta ARUNDINACEAE) Pada Konsentrasi Starter Dan Lama Fermentasi Yang Berbeda - HANDAYANI, Roro Fitri, Dr. Siti Chalimah, M.Pd (2015)
One of the innovations of yogurt with the addition of local ingredients arrowroot starch tuber. Arrowroot starch tubers contain high levels of carbohydrates as processed yogurt drinks. The purpose of this study to determine the pH and reducing sugar levels as well as the quality and acceptance of the community in yogurt arrowroot starch tuber. This research method completely randomized design (CRD) with two factors. The first factor is the volume of the starter (5 ml, 7 ml, and 9 ml) and the second factor fermentation time (4 hours, 8 hours, and 12 hours) with 3 replications replications. The results showed that the concentration and length of fermentation starter affect the pH and reducing sugar content of yogurt arrowroot starch tuber. The highest pH at a concentration of 5 ml starter and fermentation time 4 hours (Kala) is 6.04, while the lowest pH 9 ml starter concentration and fermentation time 12 hours (KcLc) is 5.26. The highest reducing sugar levels at a concentration of 9 ml starter and fermentation time 12 hours (KcLc) of 0,24%, while the lowest reduction sugar at a concentration of 5 ml starter and fermentation time 4 hours (Kala) of 0,10%. Tuber starch yogurt has less acidic flavor, aroma less savory, pale white color, soft texture, viscosity is less viscous and the majority of panelists like the taste.